Education of Native Chicken Hatching and Crossing Management in the Manuk Amertha Group, Segah Hamlet, Asahduren Village, Pekutatan Jembrana - I Gusti Agus Maha Putra Sanjaya; Ni Ketut Etty Suwitari; I Nyoman Kaca (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2022)
The demand for native chickens is increasing every year but this is not accompanied by an increase in population, especially in Bali. Manuk Amertha is a breeder group of native chickens located in Segah Hamlet, Asahduren Village, Pekutatan Jembrana. The purpose of this action research is to improve the knowledge and skills of farmers in hatchery management, crossbreeding, and the manufacture of feed additives for native chickens made from turmeric. The implementation method uses exploratory methods and active community participation. The exploratory method is carried out with a special dialogue with partners to explore all the problems experienced and the basic needs that must be addressed immediately. Specific observations and dialogues are intended to gather and identify issues in what Partner members desire. The result of this service activity is an increase in the knowledge and skills of members of the Manuk Amertha Breeder Group in hatchery management, operation of automatic hatching machines, crossing methods, and the manufacture of feed additives based on turmeric. From the service activities that have been carried out, it can be concluded that all group members have been able to understand hatchery management and operation of hatching machines well, understand the crossing method, and can make feed additives from turmeric